Acute Liver Injury Induced by Synthetic Cannabinoid Abuse - Shahbaz, Amir (Cureus, 2018)
Synthetic cannabinoid abuse can manifest with an array of unpredictable reactions ranging from sedation to hallucinations, psychosis, and seizures. Acute liver injury associated with the synthetic cannabinoid use is a rare complication. We present a case of a 22-year-old homeless male presented with abdominal pain and vomiting. He admitted regular synthetic cannabinoid use, and binge alcohol use once a week. Physical examination was remarkable only for mild icterus. The laboratory result shows abnormal liver functions tests. Viral, autoimmune, metabolic and other toxic etiologies of liver injury were ruled out. The acute liver injury was deemed to be secondary to synthetic cannabinoids toxicity. Spice-induced liver injury remains a diagnosis of exclusion after all other identifiable causes ruled out. Clinicians should have a high index of suspicion for synthetic cannabinoid abuse in a patient with acute hepatotoxicity who had a history of polysubstance abuse.